2006
DOI: 10.1210/en.2005-1178
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotropin-Inhibitory Hormone Inhibits Gonadal Development and Maintenance by Decreasing Gonadotropin Synthesis and Release in Male Quail

Abstract: Until recently, any neuropeptide that directly inhibits gonadotropin secretion had not been identified. We recently identified a novel hypothalamic dodecapeptide that directly inhibits gonadotropin release in quail and termed it gonadotropin-inhibitory hormone (GnIH). The action of GnIH on the inhibition of gonadotropin release is mediated by a novel G protein-coupled receptor in the quail pituitary. This new gonadotropin inhibitory system is considered to be a widespread property of birds and provides us with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
220
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 261 publications
(230 citation statements)
references
References 39 publications
8
220
0
2
Order By: Relevance
“…3). It may be the case that these two neuropeptides may, in combination, act on testicular development, maintenance and steroidogenesis (Ubuka et al, 2006(Ubuka et al, , 2013a.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…3). It may be the case that these two neuropeptides may, in combination, act on testicular development, maintenance and steroidogenesis (Ubuka et al, 2006(Ubuka et al, , 2013a.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates apoptotic changes in the regressed testes along with increased expression of GnIH and weak immunoreactivity of GnRH-I, pro-caspase-3 and uncleaved/full-length PARP-1. Previous studies have shown that the suppression of hypothalamic GnRH system as well as the potentiation of GnIH may lead to the suppression of pituitary LH/FSH release and also suppresses endogenous testosterone production by the Leydig cells, resulting in germ cell apoptosis (Ubuka et al, 2006(Ubuka et al, , 2013a. As yet, however, the molecular mechanism by which germ cells undergo apoptosis is not understood.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Plasma LH levels were determined by radioimmunoassay (RIA) using a highly purified chicken LH (USDA-cLH-I-3) 52 as the radioligand and standard, and polyclonal rabbit anti-chicken LH serum (USDA-AcLH-5) 52 supplied by the US Department of Agriculture-Agricultural Research Service (USDA-ARS), Biotechnology and Germplasm laboratory (Beltsville, MD). The RIA was performed as described previously 53,54 . The antiserum against chicken LH, at a final dilution of 1:50,000, exhibited the ability to specifically bind 23% of the added radioligand in the absence of any unlabelled chicken LH.…”
Section: Methodsmentioning
confidence: 99%